Nasopharyngeal Microbiome Signature in COVID-19 Positive Patients: Can We Definitively Get a Role to Fusobacterium periodonticum? - Nardelli, Carmela; Gentile, Ivan; Setaro, Mario; Di Domenico, Carmela; Pinchera, Biagio; Buonomo, Antonio Riccardo; Zappulo, Emanuela; Scotto, Riccardo; Scaglione, Giovanni Luca; Castaldo, Giuseppe; Capoluongo, Ettore (Frontiers in Cellular and Infection Microbiology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused the pandemic Coronavirus Disease 2019 (COVID-19). This virus is highly transmissible among individuals through both droplets and aerosol leading to determine severe pneumonia. Among the various factors that can influence both the onset of disease and the severity of its complications, the microbiome composition has also been investigated. Recent evidence showed the possible relationship between gut, lung, nasopharyngeal, or oral microbiome and COVID-19, but very little is known about it. Therefore, we aimed to verify the relationships between nasopharyngeal microbiome and the development of either COVID-19 or the severity of symptoms. To this purpose, we analyzed, by next generation sequencing, the hypervariable V1-V2-V3 regions of the bacterial 16S rRNA in nasopharyngeal swabs from SARS-CoV-2 infected patients (n=18) and control (CO) individuals (n=12) using Microbiota solution A (Arrow Diagnostics). We found a significant lower abundance of Proteobacteria and Fusobacteria in COVID-19 patients in respect to CO (p=0.003 and p<0.0001, respectively) from the phylum up to the genus (p<0.001). The Fusobacterium periodonticum (FP) resulted as the most significantly reduced species in COVID-19 patients respect to CO. FP is reported as being able to perform the surface sialylation. Noteworthy, some sialic acids residues on the cell surface could work as additional S protein of SARS-CoV-2 receptors. Consequently, SARS-CoV-2 could use sialic acids as receptors to bind to the epithelium of the respiratory tract, promoting its clustering and the disease development. We can therefore speculate that the significant reduction of FP in COVID-19 patients could be directly or indirectly linked to the modulation of sialic acid metabolism. Finally, viral or environmental factors capable of interfering with sialic metabolism could determine a fall in the individual protection from SARS-CoV-2. Further studies are necessary to clarify the precise role of FP in COVID-19.